2017
DOI: 10.1038/s41467-017-01051-z
|View full text |Cite|
|
Sign up to set email alerts
|

ID3 regulates the MDC1-mediated DNA damage response in order to maintain genome stability

Abstract: MDC1 plays a critical role in the DNA damage response (DDR) by interacting directly with several factors including γ-H2AX. However, the mechanism by which MDC1 is recruited to damaged sites remains elusive. Here, we show that MDC1 interacts with a helix–loop–helix (HLH)-containing protein called inhibitor of DNA-binding 3 (ID3). In response to double-strand breaks (DSBs) in the genome, ATM phosphorylates ID3 at serine 65 within the HLH motif, and this modification allows a direct interaction with MDC1. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 60 publications
3
36
1
Order By: Relevance
“…In response to double-stranded breaks, ID3 is phosphorylated by ATM. Phosphorylated ID3 accumulates at damage sites and promotes binding of MDC1 to ␥H2AX through interacting with both MDC1 and ␥H2AX (38). In this study, we found that RPL6 also accumulates at damage sites and is essential for interaction between MDC1 and ␥H2AX.…”
Section: Discussionsupporting
confidence: 53%
“…In response to double-stranded breaks, ID3 is phosphorylated by ATM. Phosphorylated ID3 accumulates at damage sites and promotes binding of MDC1 to ␥H2AX through interacting with both MDC1 and ␥H2AX (38). In this study, we found that RPL6 also accumulates at damage sites and is essential for interaction between MDC1 and ␥H2AX.…”
Section: Discussionsupporting
confidence: 53%
“…These data suggest a model in which ID4 associates with the DNA damage repair apparatus at sites of genome instability or damage via its interaction with MDC1. MDC1 was also recently found to associate with ID3, suggesting that this is a conserved feature of ID proteins (74). How MDC1 binds ID4 is unknown, however a quasi HLH domain (75) structure within MDC1 may enable interaction with the HLH domain of ID4.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in MDC1, much like BRCA1, results in hypersensitivity to double-stranded DNA breaks (Ando et al, 2013, Lou et al, 2006). MDC1 was also recently found to associate with ID3, suggesting that this is a conserved feature of ID proteins (Lee et al, 2017). MDC1 also interacted with many of the sites of chromatin interaction by ID4, and this was increased following DNA damage.…”
Section: Discussionmentioning
confidence: 96%